Mothers’ Knowledge of Reproductive Health: A Descriptive Study - irawati, Irawati; Yunus, Suwardha (PT.Mantaya Idea Batara, 2024)
Reproductive health knowledge is essential for maternal wellbeing, family planning, and public health. This study aimed to describe mothers’ knowledge of reproductive health in Bulupoddo, Sinjai. A descriptive survey design was employed, involving mothers of reproductive age as study participants. Data were collected using a structured questionnaire covering key aspects of reproductive health, including anatomy and physiology, reproductive hygiene, family planning, and prevention of reproductive health problems. Descriptive statistical analysis was applied to summarize respondents’ knowledge levels.The results showed that mothers’ knowledge of reproductive health was generally very low. In most assessed domains, the proportion of correct responses was below 50%, indicating insufficient understanding of basic reproductive health concepts. Limited knowledge was particularly evident in areas related to reproductive function, risk factors for reproductive health disorders, and appropriate preventive practices. These findings suggest that the majority of respondents had not received adequate or effective reproductive health information.In conclusion, mothers’ knowledge of reproductive health in Bulupoddo, Sinjai remains inadequate and falls below an acceptable level. This condition highlights the urgent need for comprehensive and culturally appropriate reproductive health education programs. Strengthening health promotion and community-based education, particularly through primary health care services, is essential to improve mothers’ knowledge and support better reproductive health outcomes.